Sorotan Perkembangan Terorisme Moden: Analisis Hubungan Terorisme Baharu dengan Gerakan Militan Muslim: A Review on the Development of Modern Terrorism: An Analysis of the Relationship Between New Terrorism and the Muslim Militant Movement - Mhd Nazer , Muhamad Syafriz; Che Nordin, Mohd Khairul Naim (Jurnal Usuluddin, 2021)
This paper analyzes the relationship between the concept of new terrorism and Muslim militant movements within the framework of terrorism theory along with reviews of the development of modern terrorism. Library research is applied in collecting and analyzing research data. The results show that there is a relationship between the concept of new terrorism and religions. It is based on the position of religions as a dominant factor in acts of terrorism starting in the 1990s era to the present. Muslim militant movements such as al-Qaeda, ISIS and Boko Haram are used as prime examples referring to the new characteristics of terrorism. Several aspects such as goals, tactics, activities, methods of operation, targets and threats are considered as factors that differentiate between new and old terrorism. However, the study also found that these characteristics also exist in other religious and ideologically motivated groups that operate around the world. In fact, some examples of past terrorism cases show these features have already existed before. It can thus be concluded that the concept of new terrorism should not be attributed only to the Muslim militant movement. In addition, the view of some terrorism scholars to assign a new categorization to the phenomenon of terrorism that has already occurred is an inaccurate classification and needs to be revisited.